Handbook of exploration geochemistry. Vol.3: Rock Geochemistry in Mineral Exploration - Govett, G.J.S., Ed. (Amsterdam:Elselvier Scientific Publishing Company, 1983)
Koleksi Referensi (Tidak Dipinjamkan)